A mirigyes bálványfa (Ailanthus altissima) pollenkoncentráció mérése 2019-2020 között a dél-alföldi régióban - Vojnich, Viktor József; Udvardy, Orsolya; Kajtor-Apatini, Dóra; Szigeti, Tamás; Magyar, Donát (GEORGIKON FOR AGRICULTURE, 2022)
Nowadays, there is an increasing emphasis on the problem of invasive species. In areas where the tree of heaven (Ailanthus altissima) appears and multiplies, the original vegetation degrades and transforms. The tree of heaven of great importance in urban environments, where it causes building damage, static problems and endangers utilities. In addition, it is worth mentioning that the pollen of A. altissima is an allergenic, although less important than ragweed pollen. Pollen concentration of tree of heaven was measured in three counties of the Southern Great Plain region (Bács-Kiskun county, Csongrád-Csanád county, Békés county) with the 7-day Hirst-type (Burkard) pollen trap. The highest annual total pollen count was detected in 2019 in Bács-Kiskun county (66 pieces) and Csongrád-Csanád county (36 pieces), while in Békés county (16 pieces) in 2020. In Békés county, a trap error was detected when measuring the pollen count of Ailanthus altissima in 2019, therefore the results cannot be used. Our work draws attention to the differences in the distribution of the tree of heaven in the Southern Great Plain, based on which it can be seen that there can be more than twice the differences between the cities in terms of the total annual pollen count.
Keywords: Southern Great Plain Region; tree of heaven (Ailanthus altissima); pollen concentration; allergy; building damage